Quality Assessment and storage stability of ube halaya produced in Bohol - Penales, Lara Andriza Dollisen
This study was conducted to assess the quality and storage stability of ube halaya produced by DTI-registered processor (Source A) and non-DTI-registered processor (Source B) in the province of Bohol.